Hubungan Faktor Risiko Eksternal terhadap Kejadian Otitis Media Akut pada Balita di RS Aminah Ciledug - Nanda Emira Putri, Nanda; Roito Elmina Gogo Harahap; Fasha, Ismaili; Purvis, Lailana (Universitas Muhammadiyah Prof. Dr. Hamka (UHAMKA Press), 2023)
This study examined the correlation of external risk factors to the incidence of AOM in toddlers and preschoolers. This research used an observational analytic design with a cross-sectional approach and data processing uses univariate, bivariate and multivariate analysis. Of the 61 research subjects, the majority of toddlers with AOM were 1-3 years old, 32 children (52.5%), 33 children (54.1%) were female, 37 children (60.7%) had perforation stage. 52 children (85.2%) received exclusive breastfeeding. The results showed that the four variables, including breastfeeding duration, use of pacifiers, PCV vaccinations, and history of ARI (Acute Respiratory Infection), correlated to incidences of acute otitis media. PCV vaccination and history of ARI are the most influencing variables with p-values of 0.024 and 0.006. There is a relationship between external risk factors and the incidence of AOM in toddlers, where the most influential variables are the administration of the PCV vaccine and a history of upper respiratory infection. The researcher of this study suggests at least three doses of PCV vaccination for children at the ages 2, 4, and 6 months, alongside the protection from triggers of ARI to prevent the occurrence of AOM.